2004
DOI: 10.1016/j.ydbio.2003.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Persistent expression of the ATP-binding cassette transporter, Abcg2, identifies cardiac SP cells in the developing and adult heart

Abstract: Stem cells are important in the maintenance and repair of adult tissues. A population of cells, termed side population (SP) cells, has stem cell characteristics as they have been shown to contribute to diverse lineages. In this study, we confirm that Abcg2 is a determinant of the SP cell phenotype. Therefore, we examined Abcg2 expression during murine embryogenesis and observed robust expression in the blood islands of the E8.5 yolk sac and in developing tissues including the heart. During the latter stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
451
3
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(480 citation statements)
references
References 40 publications
14
451
3
10
Order By: Relevance
“…SP cells with stem cell-like properties in adult hearts were first reported by Hierlihy et al (2002). Since then, several groups, including ours, have confirmed the presence of such stem/progenitor cell populations in adult hearts (Martin et al, 2004;Pfister et al, 2005;Oyama et al, 2007;Liang et al, 2010).…”
Section: Resident Cscs Sca1 1 /Cd31 2 Cardiac Sp Cellssupporting
confidence: 62%
“…SP cells with stem cell-like properties in adult hearts were first reported by Hierlihy et al (2002). Since then, several groups, including ours, have confirmed the presence of such stem/progenitor cell populations in adult hearts (Martin et al, 2004;Pfister et al, 2005;Oyama et al, 2007;Liang et al, 2010).…”
Section: Resident Cscs Sca1 1 /Cd31 2 Cardiac Sp Cellssupporting
confidence: 62%
“…In the bone marrow, the SP defines a cell subset with a highly homogeneous content of haematopoietic stem cells (HSCs) [69]. Similar SP cells have been detected in various organs, such as skeletal muscle [70], lung [71]; heart [72] and kidney [73,74]. Inowa et al [75] reported that an adult kidney SP fraction also exists in humans.…”
Section: Progenitors Isolated Based Upon Cellular Behaviourmentioning
confidence: 94%
“…14, 15 Hierlihy et al 14 were the first to demonstrate the presence of a verapamil-sensitive SP cell in the postnatal mouse heart. Shortly thereafter, Martin et al 15 attributed the cardiac SP phenotype to Abcg2 protein expression and showed that a population of SP cells persisted into adulthood in the mouse. When selected, adult mouse SP cells also could differentiate into α-actinin-positive cells when cocultured with primary cardiomyocytes.…”
Section: Sp Cardiac Stem Cellsmentioning
confidence: 99%